Уй пал симфония: повестьесын роман / Е. В. Самсонов - Самсонов Евгений Васильевич (Удмуртия, 1989)
Экземпляры: ф.14 (20150420) / Инвентарный номер: 51528 / Цена: 30. 00. / Сис.шифр: С(Удм) / Авт.знак: С 17 / ГРНТИ: 17.82.31 / ББК: 84(2 Рос.=Удм)-44